2020
DOI: 10.1111/jonm.13193
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness, emotional intelligence and occupational burnout in intensive care nurses: A mediating effect model

Abstract: Aim(s) To construct structural equation models to test the mediating role of emotional intelligence in the relationship between mindfulness and occupational burnout. Background Reports assessing the relationships among mindfulness, emotional intelligence and burnout, specifically in ICU nurses, are scarce. Methods This was a descriptive, correlational, cross‐sectional research design with 883 ICU nurses enrolled by convenience sampling from 29 ICUs in seven tertiary hospitals in urban areas of Chengdu, China. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 33 publications
4
29
0
5
Order By: Relevance
“…Table 2 gathers the main findings of the reviewed studies related to this review's objective [50][51][52][53][54][55][56][57][58][59].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 gathers the main findings of the reviewed studies related to this review's objective [50][51][52][53][54][55][56][57][58][59].…”
Section: Resultsmentioning
confidence: 99%
“…The reviewed studies showed a relationship between mindfulness and the ability to regulate one's emotions [52,58], emotional exhaustion [57] and EI [53,59]. The training interventions based on mindfulness have been shown to promote positive emotional balance among the participants [55], as well as emotional awareness [54], emotional acceptance, emotion recognition, identifying one's own emotions, expressive suppression [56] and the reduction of emotional exhaustion [54].…”
Section: Resultsmentioning
confidence: 99%
“…Health care organizations strive to meet increased workload during the COVID‐19 pandemic, which has led to increased job burnout of the nurses. Job burnout, a stress reaction, is identified with three dimensions: emotional exhaustion, cynicism, and professional efficacy (Maslach et al, 1996 ; Xie et al, 2020 ). Emotional exhaustion is the result of resource depletion, and an individual feels the loss of control over what happens in his/her life.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…The improvement on emotional intelligence indicated that mindfulness and emotional intelligence may share similar mechanisms. Previous studies revealed that the level of mindfulness was positively correlated with emotional intelligence 53,54,82,83 . More speci cally, the level of mindfulness could positively predict appraisal and expression of own emotion, regulation of emotion, and utilization of emotion 52,54 .…”
Section: Discussionmentioning
confidence: 93%